Strike & Rank as a way out of arbitrator conflicts of interest - Miranda Ugarte, Jean Luc Hugo (2025)
The Strike & Rank system is a method for appointing arbitrators that involves the submission of a list of potential candidates by the arbitral institution to the parties. The parties are then tasked with ranking and striking candidates based on their preferences for the administration of their arbitration. Ultimately, taking into account the preferences expressed by both parties, the institution itself makes a reasonable decision regarding the arbitrators who will preside over the arbitration. Through this system, any potential conflict of interest between the arbitrators and the parties is mitigated, as the appointed arbitrators are the result of the free and joint selection of both the claimant and the respondent.